PETROGRAPHIC CHARACTERISTICS OF ARAXÁ GROUP METASEDIMENTS IN THE ALTEROSA SUTURE PALEOZONE: HIGH-PRESSURE GRANULITIC BELT - Leme, Thaís Güitzlaf [UNESP]; Zanardo, Antenor [UNESP]; Navarro, Guillermo Rafael Beltran [UNESP] (UNESP - Universidade Estadual Paulista, 2023)
In the southwest Minas Gerais state, in the Guaxupé region, the Araxá Group occurs as an E-W to WNW-ESE belt, with approximately 20 km wide, which crops out between the Barbacena Complex and the Guaxupé Complex, in the Alterosa Suture Paleozone. This paper presents petrographic lithologies and metamorphic assemblage characterization of the metasedimentary rocks that occur between the Varginha (VSZ) and Campos Gerais (CGSZ) shear zones, located in the southern portion of this belt. In the study area, the Araxá Group is composed of pelitic, psammo-pelitic and graywacke metasedimentary rocks, represented by paragneisses, quartz schists, and quartzites bearing garnet, kyanite, orthoclase, oligoclase/andesine, and rutile. The metamorphic peak paragenesis is pre to early main foliation (Sn) development and indicates high-pressure granulite facies conditions, with minimum temperatures of the order of 800ºC, in the kyanite stability field. These paragenesis were superimposed by mineral assemblages from metamorphic reequilibration in granulite to upper amphibolite facies conditions, during the Sn foliation development. The metamorphic P-T path is clockwise. The metasedimentary rocks that occur between the VSZ and CGSZ represent a high-pressure granulitic belt.
CARACTERÍSTICAS PETROGRÁFICAS DOS METASSEDIMENTOS DO GRUPO ARAXÁ NA REGIÃO DA PALEOZONA DE SUTURA DE ALTEROSA: CINTURÃO GRANULÍTICO DE ALTA PRESSÃO
Keywords: Alterosa Suture Paleozone; High-pressure granulite; Metasediments; Petrography; Southern Brasília Belt